Patient-Centered Care In Ophthalmology: Integrating Nursing Principles With Optic Technician Practices (Journal of Namibian Studies : History Politics Culture, 2022)
Patient-centered care in ophthalmology emphasizes the importance of tailoring eye care services to meet the unique needs and preferences of individual patients. This paper explores the integration of nursing principles into optic technician practices to enhance patient-centered care delivery. Key nursing principles, including communication, empathy, and holistic care, are identified and discussed in the context of their applicability to optic technician roles. Strategies for integrating these principles into optic technician practices are explored, along with the benefits and challenges of collaborative care between nursing and optic technician teams. Through a collaborative approach, ophthalmic healthcare providers can improve patient outcomes, satisfaction, and overall quality of care.